Challenges of social auditing in China: from the social auditors’ perspective - Chow, Lowell (2009)
Drawing upon a series of interviews conducted with social auditing practitioners in the mainland China, this study aims at identifying challenges that social auditors face when they perform social audits. Results are analyzed and categorized into four themes, namely the hide-and-seek game, bribery and threats, cultural differences and commercial relationship. These concerns not only suggest what could be expected when performing social auditing in China, but also provide another dimension of evidence for the doubts towards the belief in social auditing as a strong tool for demonstrating corporate social accountability.